1999
DOI: 10.1021/ic9808549
|View full text |Cite
|
Sign up to set email alerts
|

[CuCN·Me3SnCN·C4H4N2]:  A Threefold- Interpenetrating, Distorted-Diamondoid Framework (C4H4N2 = Pyrazine)

Abstract: Notably distorted, adamandoid Cu10 cages with Cu···Cu edges of 10.795(6) Å (Cu−CN−Sn(Me3)−NC−Cu) and 7.142(5) Å (Cu−pyrazine−Cu) are the basic building blocks of the novel supramolecular assembly [CuCN·Me3SnCN·C4H4N2] (C4H4N2 = pyrazine). Interpenetration of three equivalent, distorted-diamondoid frameworks affords comparatively compact crystal packing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 12 publications
(16 reference statements)
0
27
0
Order By: Relevance
“…The case which is supported by X-ray results indicating bent CuCN groups (C3-Cu2-C9 = 127.07 o ). This is further supported by the fact that the frequencies of the t CN appear at more or less the same position of the prototype compounds [41][42][43][44].…”
Section: Ir-and 1 H-nmr-spectra Ofmentioning
confidence: 62%
“…The case which is supported by X-ray results indicating bent CuCN groups (C3-Cu2-C9 = 127.07 o ). This is further supported by the fact that the frequencies of the t CN appear at more or less the same position of the prototype compounds [41][42][43][44].…”
Section: Ir-and 1 H-nmr-spectra Ofmentioning
confidence: 62%
“…26 The latter finding reflects the fact that the MOFs 1-5 should not have similar structures in spite of the fact that they have the same chemical formulae as well as their structures are different from that of [Me 3 SnCu(CN) 2 •pyz]. 26 However, the MOFs 1 and 2 seem to be isostructural since they have the same reflections.…”
Section: Structures Of the Mofs 1-5mentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27] It has been shown that organometallic R 3 E + units (R=Me, Et, n-propyl, n-butyl, phenyl; E=Sn, Pb) can bridge the cyanometallate anions, M(CN) n q-, in much the same fashion as silver do in SPB 28 except that the greater complexity of the R 3 E + units leads to complicated three-dimensional polymer. 26,27,[29][30][31] The supramolecular interplay of the Ph 3 Sn + unit and the tetrahedral [Cu(CN) 4 ] 3-ion with either pyz, mepyz, bpy, tbpe, or bpe as bidentate ligands (L) in presence of H 2 O affords the products [(Ph 3 Sn) 3 Cu(CN) 4 •L•XH 2 O]. 27 The water molecules are usually coordinated to tin atoms and are involved in two significant O-H-N hydrogen bonds, wherein the nitrogen atoms belong either to the bidentate ligand or the M-coordinated cyanide ligands.…”
Section: Introductionmentioning
confidence: 99%
“…groups on the topology of the SCP. However, the structure features of these SCP are the formation of 3D-networks which contain the rhombic [Cu 2 (l 3 -CN) 2 ] motif or strong Cu…Cu interaction, even shorter than in elemental copper, via interwoven of the sheets [7][8][9]. Such porous networks have potential applications in areas such as separations, gas storage, antitumor, luminescence and catalysis [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Pb(Me 3 ) / NC-Cu-]-, which create voluminous 3D-networks wherein one carbon atom of each [CNPb(Me 3 )NC] spacer interacts with a pair of copper ions. The structure of 1 is quite different than that of [CuCN Me 3 SnCN pyz], 2[8]. The basic sub-units of 2 consist of distorted-adamandoid Cu 10 cages whose surfaces are surrounded either by [Cu 6 (pyz)4 {Sn-(NC) 2 } 2 ] or by [Cu 6 (pyz) 2 {Sn(NC) 2 } 4 rings.…”
mentioning
confidence: 99%